2003
DOI: 10.1002/polb.10486
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the micromechanical deformation behavior of styrene–butadiene star block copolymer/polystyrene blends with high‐voltage electron microscopy

Abstract: The deformation behavior of blends consisting of a styrene–butadiene star block copolymer and a polystyrene homopolymer was studied by high‐voltage electron microscopy with a tensile device. The mechanical properties and micromechanical deformation mechanisms in the star block copolymer/polystyrene blends were directly influenced by their morphology. Although the pure block copolymer deformed in a very unequal manner (because of a thin‐layer‐yielding mechanism) and revealed no local deformation zones, a transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…The morphology of blends of an SB star block copolymer and PS, which ranges from microphase‐separated to macrophase‐separated structure depending on the molecular weight of the PS and the composition of the blends clearly affects the tensile mechanical properties . Material‐specific correlations between the morphology, the mechanical properties and the microdeformation behaviour have been also found for other SB star block copolymer/PS blends . One of our papers also deals with morphology–toughness correlations of blends composed of a SB star block copolymer (ST3) and PS homopolymer (ST3 has three short arms in average and one longer arm).…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…The morphology of blends of an SB star block copolymer and PS, which ranges from microphase‐separated to macrophase‐separated structure depending on the molecular weight of the PS and the composition of the blends clearly affects the tensile mechanical properties . Material‐specific correlations between the morphology, the mechanical properties and the microdeformation behaviour have been also found for other SB star block copolymer/PS blends . One of our papers also deals with morphology–toughness correlations of blends composed of a SB star block copolymer (ST3) and PS homopolymer (ST3 has three short arms in average and one longer arm).…”
Section: Introductionmentioning
confidence: 78%
“…[6] Another study on four arm SB star block copolymer/ PS homopolymer (hPS) blends has revealed that the hardness increased with the increase in the PS-layer thickness. [7] The mechanical behaviour [8][9][10][11][12][13] and morphology [8][9][10][11][12][13][14][15][16][17] of blends of SB block copolymers and hPS have been repeatedly investigated in the last decade, mainly by Adhikari el al. [8][9][10][11][12][13][14] The morphology of blends of an SB star block copolymer and PS, which ranges from microphase-separated to macrophaseseparated structure depending on the molecular weight of the PS and the composition of the blends clearly affects the tensile mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that during solution polymerization Bd reacts first in the system, and the product in the end is a tapered block polymer since the reactivity ratios of the monomers vary widely at room temperature . To avoid the block of St, the polarity regulator was introduced into the reaction system.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, blends of block copolymers and a homopolymer belong to a technologically highly important class of materials, and their mechanical and rheological properties are intensively studied. [7][8][9][10][11] Since processing of polymers is intimately related to the melt rheology in shear and elongation, a series of studies investigated the flow behavior and the deformation of pure block copolymers and related blend systems. [12][13][14][15][16][17][18][19][20] Besides the knowledge of the shear and extensional viscosity, additional elongational properties such as strain-hardening and melt stability are of interest for technological applications.…”
Section: Introductionmentioning
confidence: 99%